The philosophy of tacit knowledge : the tacit side of knowledge management in organizations - Johannessen, Jon-Arild (Emerald Publishing Limited, 2022)
Knowledge management expert Jon-Arild Johannessen presents a comprehensive exploration of tacit knowledge based on the research problem: How can tacit knowledge be used to improve organizational performance in practice? To explore this problem, 50 short cases are presented and discussed to analyze and reflect on what tacit knowledge is, how it is developed, transferred and integrated, to improve performance. Tacit knowledge is hard to codify and specify, yet these short cases will demystify how tacit knowledge works in organizations and the benefits of it in relation to improving productivity and processes. The emphasis on short, easy to connect with cases in The Philosophy of Tacit Knowledge allows readers to develop their own models and policy strategies towards improving their own practice.
Keywords: Tacit knowledge.; Knowledge management.; Psychology -- Cognitive Neuroscience & Cognitive Neuropsychology.; Philosophy: epistemology & theory of knowledge.; elektronické knihy; electronic books